2006
DOI: 10.17795/mejrh-43200
|View full text |Cite
|
Sign up to set email alerts
|

Knee Osteoarthritis: Condroprotector Action and Symptomatic Effect of Ozone on Pain, Function, Quality of Life, Minimal Joint Space and Knee Arthroplasty Delay

Abstract: Objectives: To evaluate the effect of Ozone on pain, function, quality of life, minimal joint space and knee arthroplasty delay in a case series of patients with knee osteoarthritis (OA). Methods:Prospective quasi-experimental before-after study on 52 out of 120 patients with knee osteoarthritis (OA) Kellgren-Lawrence (K-L) grade 2 or more, who attended Santa Cristina's University Hospital, from January 2012 to June 2016. The Ozone protocol consisted of four sessions (1 session/week) of an intra-articular infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…After 1 year of follow-up and two treatment cycles, ozone (O2-O3) has been able to increase the minimum joint space of the medial compartment of both knees, as has been observed radiologically (from 2.9 to 4.6 mm in the right knee and from 3.4 to 4 mm in the left knee), reversing knee osteoarthritis in our patient. This finding confirms the disease-modifying effect of ozone (O2-O3) on osteoarthritis of the knee, findings that coincide with what was recently reported by Fernández-Cuadros et al [9]. For the first time, this case report shows that ozone (O2-O3) is a drug capable of producing structural (anabolic) changes in knee osteoarthritis.…”
Section: Discussionsupporting
confidence: 92%
“…After 1 year of follow-up and two treatment cycles, ozone (O2-O3) has been able to increase the minimum joint space of the medial compartment of both knees, as has been observed radiologically (from 2.9 to 4.6 mm in the right knee and from 3.4 to 4 mm in the left knee), reversing knee osteoarthritis in our patient. This finding confirms the disease-modifying effect of ozone (O2-O3) on osteoarthritis of the knee, findings that coincide with what was recently reported by Fernández-Cuadros et al [9]. For the first time, this case report shows that ozone (O2-O3) is a drug capable of producing structural (anabolic) changes in knee osteoarthritis.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, Fernandez-Cuadros et al demonstrated that in the long-term follow-up period of 10 to 28 months that ozone was capable of increasing medial and lateral minimal joint space at the knee in 52 OA patients (10). Ozone was also capable of delaying knee arthroplasty replacement to an extent that none of the patients went to definitive surgical procedure (10).…”
Section: Argumentsmentioning
confidence: 99%
“…The arguments of this article are based on three previous quasi-experimental before-and-after studies published by the study group and with a level of evidence 2b (6,9,10). Scientists are encouraged to replicate the current promising findings for the management of knee OA.…”
Section: Argumentsmentioning
confidence: 99%
“…The lower the JSW, the greater the knee OA severity (5). That correlation is only valid for the medial compartment, because for the lateral compartment, the greater the JSW, the greater the OA severity (6). The JSW usually narrows in the weightbearing compartment (mainly medial), and it widens in the contralateral compartment (frequently lateral) (7-9), phenomena known as the yawn sign (2).…”
Section: To the Editormentioning
confidence: 99%